Case Report: Application of the AngioJet thrombectomy system in acute lower extremity deep vein thrombosis complicated by transplanted renal vein thrombosis (report of two cases) - Shao, Lifan; Cao, Guangxin; Shang, Suiyuan; Sun, Bo; Ji, Wuguang; Zhang, Jiefeng; Liu, Tao (Frontiers in Cardiovascular Medicine, 2025)
Lower extremity deep venous thrombosis (DVT) combined with transplanted renal vein thrombosis represents a rare and complex form of venous thromboembolism that leads to obstruction of the transplanted renal vein. This condition results in parenchymal edema of the kidney, ultimately impairing the function of the transplanted organ. It constitutes a catastrophic complication following renal transplantation, potentially resulting in loss of function of the transplanted kidney and failure of the surgical procedure. The primary objective of treatment is to promptly remove thrombi from the transplanted renal vein, thereby restoring normal venous return and renal function as swiftly as possible to enhance patient prognosis. Currently, surgical thrombectomy and thrombolytic therapy are considered the mainstay treatment modalities. Surgical thrombectomy is generally recommended as a first-line approach due to its efficacy in achieving rapid thrombus removal. To date, there exists limited literature regarding the utilization of the AngioJet thrombectomy system for managing DVT in conjunction with transplanted renal vein thrombosis. In this report, we present two cases involving middle-aged male patients diagnosed with acute lower extremity DVT complicated by transplanted renal vein thrombosis. Both patients had undergone allogeneic kidney transplantation 15 and 4 years prior, respectively. In these instances, we employed the AngioJet thrombectomy system for emergency thrombus aspiration treatment. The thrombi within both patients' lower extremity deep veins and their respective transplanted renal veins were completely removed. Subsequently, urine output gradually increased for both patients; moreover, their renal function progressively improved to an acceptable range. Notably, neither patient developed postoperative complications nor exhibited any recurrence of thrombi during follow-up evaluations.